Education in the Tacna region in times of pandemic due to COVID-19 - Cohaila Quispe, Carmen Rosa (2024)
This article aims to determine how access to digital tools influences the development of an equitable education in students with the "I learn at home" strategy, implemented by the Ministry of Education of Peru in times of the COVID-19 pandemic, in primary and secondary education students in the Tacna Region. The problem presented in this study was based on how students in the Tacna Region access digital tools in the current context, thus, two research questions were posed, which were analyzed from direct observation and for this analysis, 10 aspects were considered and it was observed with the analysis of the drawings that there are still differences in how they access educational content in public and private institutions, obtaining as results that there is no equity in access to digital tools. It is important that students have the necessary technological tools and in this way shorten the gap that exists between digital tools and connectivity, because only in this way can we achieve the goal of an education with equity and for all.